Mood instability and risk of gastrointestinal diseases - a univariable and multivariable mendelian randomization study - Rui-lin Liu; Qing-chun Song; Li-ming Liu; Yi-feng Yang; Wei-hong Zhu (Annals of General Psychiatry)
Abstract Background Mood instability, characterized by sudden and unpredictable mood shifts, is prevalent in psychiatric disorders and as a personality trait. Its association with gastrointestinal diseases has been recognized but remains poorly understood in terms of causality. Methods This study aims to investigate the causal relationship between mood instability and a spectrum of gastrointestinal diseases by univariable and multivariable mendelian randomization analysis. The exposure and outcome data were retrieved from the IEU open GWAS database, the UK biobank and the FinnGen study. Instrumental variables were selected to meet relevance, independence, and exclusion restriction criteria. GWAS datasets for mood instability and 28 gastrointestinal diseases were utilized, incorporating diverse populations and genders. Univariable and multivariable Mendelian randomization analyses were conducted using R software. MR statistics from different datasets for the same disease were meta-analyzed to maximize the study population. Results In univariable MR analysis, genetic predisposition to mood instability showed significant associations with increased risk for several gastrointestinal diseases, including: gastroesophageal reflux disease, gastric ulcer, acute gastritis, irritable bowel syndrome, internal hemorrhoids, cirrhosis, cholecystitis, cholelithiasis, acute pancreatitis, chronic pancreatitis. In multivariable MR analysis, after adjusting for major depression, bipolar disorder, anxiety disorder, and schizophrenia, associations with the following gastrointestinal diseases remained statistically significant: internal hemorrhoids, cirrhosis, acute pancreatitis, chronic pancreatitis. Conclusion This study provides compelling evidence for a potential causal relationship between mood instability and certain gastrointestinal diseases underscoring the importance of considering mood instability as a potential risk factor for gastrointestinal diseases as well as the positive role of maintaining mood stability in the prevention of gastrointestinal disorders.